High-T c superconductivity in undoped ThFeAsN - T. Shiroka (Nature Portfolio, 2017)
Exploring the interplay between the superconducting gap and the antiferromagnetic phase in Fe-based superconductors remains an open issue. Here, the authors show that Fermi-surface modifications by means of structural distortions and correlation effects are as important as doping in inducing superconductivity in undoped ThFeAsN.